2018
DOI: 10.1016/j.jtcvs.2017.09.150
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after near-infrared sentinel lymph node mapping in non–small cell lung cancer

Abstract: Patients with pN0 SLNs showed favorable disease-free and overall survival. This preliminary review of NIR SLN mapping in NSCLC suggests that pN0 SLNs may better represent true N0 status. A larger clinical trial is planned to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Some studies [22] have shown that patients with positive results of sentinel lymph node biopsy followed by lymph node dissection may have a better prognosis. Direct lymph node dissection without sentinel lymph node biopsy may cause more complications and affect the long-term prognosis of patients [23,24]. Based on these results, sentinel lymph node biopsy after surgical resection of the tumor may be a better way.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [22] have shown that patients with positive results of sentinel lymph node biopsy followed by lymph node dissection may have a better prognosis. Direct lymph node dissection without sentinel lymph node biopsy may cause more complications and affect the long-term prognosis of patients [23,24]. Based on these results, sentinel lymph node biopsy after surgical resection of the tumor may be a better way.…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly targeted agents (ie, tyrosine kinase inhibitors for EGFR ‐mutated cancer, BRAF inhibitors, ROS1 inhibitors, etc) and immunotherapy agents (pembrolizumab, nivolumab, ipilimumab, atezolizumab, etc) are being used to treat more advanced NSCLC and thus to treat cases of nonresectable LRR . Perhaps more important are the emerging technologies being developed to prevent LRR in NSCLC, namely, more accurate staging using near‐infrared lymphatic mapping to more accurately identify SLNs and the placement of brachytherapy seeds at the staple line after sublobar resections . Although identifying SLNs is not technically a therapeutic intervention, no LRR occurred in patients who had a negative SLN identified using this technique, and their DFS was superior compared with patients who were staged using standard lymphadenectomy ( P = .036) .…”
Section: Non–small Cell Lung Cancermentioning
confidence: 99%
“…Perhaps more important are the emerging technologies being developed to prevent LRR in NSCLC, namely, more accurate staging using near‐infrared lymphatic mapping to more accurately identify SLNs and the placement of brachytherapy seeds at the staple line after sublobar resections . Although identifying SLNs is not technically a therapeutic intervention, no LRR occurred in patients who had a negative SLN identified using this technique, and their DFS was superior compared with patients who were staged using standard lymphadenectomy ( P = .036) . The American College of Surgeons Oncology Group Z4032 phase 3 trial randomized 222 patients with stage I NSCLC to undergo sublobar resection versus sublobar resection with brachytherapy seeds placed at the suture line, and there was a nonsignificant trend toward decreased local recurrence with brachytherapy in those who had positive staple‐line cytology (HR, 0.22; P > .05) …”
Section: Non–small Cell Lung Cancermentioning
confidence: 99%
“…These trials resulted in a greater than 80% detection of NIR-positive SLN(s) without adverse events and identified metastatic disease exclusively within the SLN in several patients. 4,5 The fluorescence itself is physiologically independent of disease status and is intended to function as an anatomical indicator of the most clinically relevant node (ie, the first tumor-draining lymph node). To reach tumors of varying sizes and locations, several approaches have been developed for peritumoral indocyanine green injection, including transthoracic injection for palpable tumors and navigational bronchoscopy–guided (Figure) or intraoperative computed tomography–guided injections for small, ill-defined early-stage tumors.…”
Section: What Is the Innovation?mentioning
confidence: 99%
“…This study also demonstrated that in-depth analysis of the SLN can facilitate identification of occult metastatic disease, leading to upstaging and early initiation of chemoradiotherapy. Previous studies using SLN mapping in NSCLC focused on techniques and SLN yield; however, a recent report 5 on long-term outcomes of NIR-identified SLN(s) demonstrated a statistically significant improvement in disease-free survival in patients with a pathologically negative SLN over patients who underwent standard lymph node sampling. Although further study with larger numbers of patients is required to validate this report, these results highlight the potential benefits of SLN mapping in patients with NSCLC.…”
Section: Is There Evidence That Supports the Benefits Of The Innovation?mentioning
confidence: 99%